Comparison between postures of meditation Theravada Buddhism and Taoism - M. D. D. I. GUNATHILAKE (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: The primary goal of this research is to examine the similarities and differences between Taoist and Theravada Buddhist approaches to sitting and walking meditation in light of their potential applications in treating mental and physical illness in modern society.Method: The primary methodological strategy used to examine the central argument of this study is historiography. This study’s content analysis relies heavily on primary sources like archival materials and documents and a wide range of scholarly arguments.Findings: People’s physical and mental well-being have been shown to improve through both sitting and working meditation, even in today’s stressful, competitive, complicated, and market-oriented society. A recent explosion in popularity shows that the highest-ranking professionals and wealthiest people are practising sitting and working meditation to improve their health and productivity. It’s not just a fad sweeping the nation; it’s a worldwide phenomenon. People in countries that don’t practise Buddhism or Taoism, like those in Europe, have been innovating by meditating for the same benefits.Implications/Novel Contribution: The increasing prevalence of non-epidemic diseases as a result of mental stress highlights the relevance of this study in several ways for the modern world. Both of these seated meditation positions have been shown to have beneficial effects on stress and physical health. In addition, this leads to the simplification of all manner of mundane, real-world tasks. The results of this study can be used by academics who plan to focus their careers on studying meditation and postures.